Deteksi Bukti Digital Game Online pada Platform Skyegrid Menggunakan Framework FRED - Ramansyah Ramansyah; Yudi Prayudi; Imam Riadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Cloud gaming services provide access to high-specification online games, but can be accessed with a minimalist device. The ease of access invites new crimes and challenges violations that are found to find digital clues and evidence in uncovering cases of crimes that occur. The cloud forensic science approach remains a challenge for investigators because each cloud provider, especially cloud gaming services, has a different architecture so that further research is needed in carrying out cloud gaming forensics services. Various frameworks have been proposed by previous researchers, one of which is the Framework for Reliable Experimental Design (FRED) framework. The focus of this research is to show digital evidence of crime on the Skyegrid cloud gaming services platform by implementing FRED work steps. The important findings of this research are username, password login on Skyegrid, and log.txt file which describes the history of access to Skyegrid and online game.